Making Accreditation with English in Daily Conversations - Reza Pishghadam; Shima Ebrahimi; Saba Hasanzadeh; Haniyeh Jajarmi (Applied Research on English Language, 2022)
Since language is an integral part of a culture, inspecting linguistic expressions can unveil the hidden cultural memes of a society, conceptualized as cultuling (culture in language) analysis. The present study examined the cultuling of ‘making accreditation with English’ used by Persian native speakers from the upper, middle, and lower social classes. To this end, 623 pieces of natural utterances, embracing this cultuling, were extracted from people's conversations in public and private places and from Iranian movies. Then, 279 utterances were analyzed from linguistic, cultural, and psychological perspectives based on the cultuling analysis (CLA) model. Additionally, more data were acquired through semi-structured interviews with 198 participants aged 19 to 54. The results of the study revealed that Iranians use English for various purposes in their conversations, including accreditation, power, education, superior identity, and higher social class in public/ private and formal/ informal contexts. Moreover, the analysis of Iranians’ different reactions to hearing English words in conversations manifested their hidden cultural patterns, including indirectness, power distance, uncertainty avoidance, high context, collectivism, low trust, and overstating